EVOLUTION OF THE PRODUCTION AND PRICE OF FOREST BIOMASS FOR ENERGY - Sozinho, Thiago Manoel; Buratto, David Alexandre; dos Santos, Anadalvo Juazeiro; Garzel Leodoro da Silva, João Carlos; Frega, José Roberto (Floresta, 2018)
This study aimed to analyze the evolution of the production and price of biomass from native and planted forests of the state of Paraná (Brazil), between 1998 and 2015, based on the behavior of the prices of the products, according to variations of their supply or demand. The annual rates for growth of the price and quantity produced were calculated and related to the displacements of the supply and demand curves of the products. The results indicated a decrease in the quantity and an increase in the biomass price for native forests, which caused a shift in the supply curve to the left. For the biomass of planted forests, the demand curve shifted to the right due to the demand increase of this product for energy production. The behavior of both curves indicated a substitution of the biomass from native forests to biomass from planted forests due to factors related to the increase of environmental protection regarding the native forests located in the state of Paraná